(3GdGcJaG aj eZGRj GdeUWai hGdKdGKI GdNdaGs - (3GdcdGYj , SdjeGf Hf ehSi Hf SGde Hf MSGf GdMejQj, CHh GdQHjY,J (B634 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj ef YdjfG HGdESdGe s
(3BNQgG (B:s
(3BNQg eHJhQ hBNQ eG ajg (B: (3hNQL GdeSdehf Ydi QhGjGJge hUahage adeG CcKQhG YfOgG CeQ GdNjd s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B136 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B399s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B371 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B634 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B43 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs